A real-life assessment on the effect of smart appliances for shifting households' electricity demand. (1st June 2015) - Kobus, Charlotte B.A.; Klaassen, Elke A.M.; Mugge, Ruth; Schoormans, Jan P.L.
Highlights: Households shift demand of the washing machine away from the evening peak. Households do their laundry more often when electricity is locally produced. Users of automation shifted most demand. Abstract: Today's major developments in the production and demand of electricity in domestic areas make it increasingly important that domestic electricity demand can respond to the availability of electricity. Energy management systems and smart appliances can facilitate this by supporting the user to shift electricity demand of appliances to moments in time when electricity is abundantly available. However, the benefits resulting from domestic demand response depend on household acceptance and behaviour change. This paper explores the real electricity demand shift of households in time and the role of smart appliances to bring about this shift. A longitudinal study was conducted among Dutch households over a period of one year. The households received a dynamic electricity tariff, an energy management system and a smart washing machine. Results show that households shift their usage of the smart washing machine mostly to the day when the sun is shining and electricity is produced by their own solar panels. Households who regularly used automation of the smart washing machine, which implicates that the use of the washing machine is automatically shifted to time periods where electricity supply is abundantly available, were more likely to shift their electricity usage. Furthermore, during the course of one year, the results remained stable, indicating a structural shift in demand.